Targeted mutagenesis of EOD3 gene in Brassica napus L. regulates seed production. Issue 3 (25th August 2020) - Khan, Muhammad H. U.; Hu, Limin; Zhu, Miaoshan; Zhai, Yungu; Khan, Shahid U.; Ahmar, Sunny; Amoo, Olalekan; Zhang, Kunpeng; Fan, Chuchuan; Zhou, Yongming
Abstract: Seed size and number are central to the evolutionary fitness of plants and are also crucial for seed production of crops. However, the molecular mechanisms of seed production control are poorly understood in Brassica crops. Here, we report the gene cloning, expression analysis, and functional characterization of the EOD3/CYP78A6 gene in rapeseed. BnaEOD3 has four copies located in two subgenomes, which exhibited a steady higher expression during seed development with differential expression among copies. The targeted mutations of BnaEOD3 gene were efficiently generated by stable transformation of the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeat) vector. These mutations were stably transmitted to T1 and T2 generations and a large collection of homozygous mutants with combined loss‐of‐function alleles across four BnaEOD3 copies were created for phenotyping. All mutant T1 lines had shorter siliques, smaller seeds, and an increased number of seeds per silique, in which the quadrable mutants showed the most significant changes in these traits. Consequently, the seed weight per plant in the quadrable mutants increased by 13.9% on average compared with that of wild type, indicating that these BnaEOD3 copies have redundant functions in seed development in rapeseed. The phenotypes of the different allelic combinations of BnaEOD3 copies also revealed gene functional differentiation among the two subgenomes. Cytological observations indicated that the BnaEOD3 could act maternally to promote cotyledon cell expansion and proliferation to regulate seed growth in rapeseed. Collectively, our findings reveal the quantitative involvement of the different BnaEOD3 copies function in seed development, but also provided valuable resources for rapeseed breeding programs. Abstract : We report the gene cloning, expression analysis, and functional characterization of the EOD3/CYP78A6 gene in rapeseed. The seed weight per plant in the quadrable mutants increased by 13.9% on average compared with that of wild type. Our findings reveal the quantitative involvement of the different BnaEOD3 copies function in seed development.